2019
DOI: 10.1186/s12967-019-1934-z
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-day at symptom onset was not associated with infarct size and long-term prognosis in patients with ST-segment elevation myocardial infarction

Abstract: Background ST-segment elevation myocardial infarction (STEMI) displays circadian variability with the highest incidence in the morning hours. Data on whether the time-of-day at symptom onset affects infarct size or patients’ long-term prognosis are conflicting. We sought to investigate the association of time-of-day at symptom onset with infarct size or long-term mortality in patients with STEMI undergoing primary percutaneous coronary intervention (PPCI). Methods This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…15 Moreover, hemodynamic stress (i.e., alterations in blood pressure) and increased sympathetic activity in the morning may also contribute to the higher risk for stroke by inducing plaque rupture. 2,16,17 Among this study population, we also found that stroke onset during 00:00 to 06:00 and 06:00 to 12:00 was associated with higher proportion of favorable outcomes at 3 months. One of the factors that may contribute to this result is the circadian variation in the penumbra area.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…15 Moreover, hemodynamic stress (i.e., alterations in blood pressure) and increased sympathetic activity in the morning may also contribute to the higher risk for stroke by inducing plaque rupture. 2,16,17 Among this study population, we also found that stroke onset during 00:00 to 06:00 and 06:00 to 12:00 was associated with higher proportion of favorable outcomes at 3 months. One of the factors that may contribute to this result is the circadian variation in the penumbra area.…”
Section: Discussionmentioning
confidence: 58%
“…15 Moreover, hemodynamic stress (i.e., alterations in blood pressure) and increased sympathetic activity in the morning may also contribute to the higher risk for stroke by inducing plaque rupture. 2,16,17…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Tödt et al [ 15 ], who found a correlation between FMC and myocardial injury in STEMI patients treated with pPCI [ 15 ]. Furthermore, studies of infarct size, left ventricular function, and prognosis in women compared to men did not show significant differences [ 16 ], and the time of day of symptom onset was also not a significant variable [ 17 ]. On the contrary, we found that males were almost 13 times more likely to have a larger infarct site then females.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have analysed short-term in-hospital, 30-day or 1-year mortality. Recently, Sager and colleagues [ 14 ] reported that time-of-day at symptom onset was neither associated with infarct size nor with 5-year mortality in patients with STEMI undergoing PPCI. However, in their study, STEMI patients enrolled between 2002 and 2007 were not be the most contemporary STEMI cohort with respect to stent technology and anti-platelet therapy; and only 37% patients finished 5-year follow-up.…”
Section: Discussionmentioning
confidence: 99%